DERMATITIS KONTAK ALERGIK AKIBAT TATO TEMPORER PADA PASIEN RAWAT JALAN DI RSUP SANGLAH DENPASAR PADA TAHUN 2010 - Desy Wulandari; IGK Darmada; IGN Darma Putra (Intisari Sains Medis, 2015)
Allergic contact dermatitis in Sanglah General Hospital still becomes one of the highest number of disease. There are several factors which makes this disease appear, such as: the chemical content which contains in particular cosmetics, parfume, or temporary tattoo which can change into allergen that can stimulates inflamation response . As the tourism object which has a lot of culture and arts just like temporary tattoos, which is very popular as an alternative in changing the permanent one. But, nowadays the temporary tattoos often use the chemical contents which can stimulates the inflammation reaction on the skin which more familiarly known as allergic contac dermatitis. There are some kinds of chemical contents , such as: parafenilandiamine, which is almost the same as the strong sensitizer. This chemical content is often used in temporary tattoo.Â